Beyond Policy Rhetoric: Principal’s Concerns in Implementing Emancipated Curriculum in a Private Madrasah in South Sumatra - Amalia Hasanah; Tri Hermawan Aini; Ridho Saparudin (Program Studi Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2026)
The Emancipated Curriculum in Indonesia promotes flexibility and student-centered learning, yet its implementation in private madrasahs remains underexplored, particularly from the principal’s perspective. While existing studies focus on teacher readiness or public madrasahs, little is known about how private madrasah principals navigate structural and pedagogical constraints after multiple years of implementation. This qualitative single-case study addresses that gap by examining the implementation of the Emancipated Curriculum and the principal’s concerns at one private madrasah in South Sumatra. Data were collected through semi-structured interviews with the principal, who has led the madrasah for six years, and analyzed using reflexive thematic analysis. The findings reveal three key patterns: (1) despite proactive teacher training, formative initial assessments, and differentiated instruction remaining inconsistently applied; (2) the development of the Madrasah Operational Curriculum excludes parents and community representatives, reflecting governance isolation; and (3) project-based learning under P5 PPRA is limited to three recurring themes due to resource constraints, and textbooks are unavailable for some subjects. These patterns indicate that structural support, rather than training alone, determines curriculum fidelity. The study contributes a principal-centered, private-madrasah perspective to the curriculum reform literature and highlights the need for systemic alignment of resources and inclusive governance in Islamic educational contexts.